Impact of the time from the completion of neoadjuvant chemotherapy to surgery on the outcomes of patients with gastric cancer - Wu, Chaorui; Zhou, Hong; Wang, Tongbo; Zhang, Xiaojie; Chen, Yingtai; Zhao, Dongbing (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Gastrectomy is usually recommended within 5 to 6 weeks after the completion of neoadjuvant chemotherapy (NCT). However, the optimal timing of surgery is not clearly defined. Methods: This study retrospectively reviewed the clinical records of 229 patients with locally advanced gastric cancer (GC) who underwent curative gastrectomy after NCT between 2006 and 2016. The effect of the time to surgery (TTS), defined as ≤4, 5–6, and >6 weeks, on patient outcomes was examined. Descriptive statistics and Cox proportional hazards models were used. Results: Seventy of 229 patients (30.6%) had surgery within 4 weeks after their last dose of NCT, 103 (45.0%) within 5–6 weeks, and 56 (24.5%) after 6 weeks. The median age was 56.0 [interquartile range (IQR), 47.0–63.0] years, and the median TTS was 34.0 (IQR, 26.0–42.0) days. The three groups did not significantly differ regarding most surgical and histopathological characteristics except for the NCT regimen (P=0.010), number of cycles of NCT (P=0.017) and pathological stage (P=0.015). The NCT regimen was the only independent factor associated with TTS >6 weeks (P=0.015). The 3-year progression-free survival (PFS) estimates were 41.9%, 42.8% and 61.7% in patients who underwent surgery in ≤4, 5–6, and >6 weeks after NCT, respectively (P=0.044). The 3-year overall survival (OS) estimates were 57.7%, 58.0% and 68.2% in the three groups, respectively (P=0.202). According to multivariable analysis, compared with the interval of ≤4 weeks, patients who underwent surgery at 5–6 or >6 weeks had equivalent PFS and OS. Conclusions: The NCT-surgery interval time has no impact on patient outcomes.